Degradation Study of C.I. Reactive Yellow 145 by Advanced Oxidation Process - Hussain Bokhari, Tanveer; Kashif, Muhammad; Ahmad Bhatti, Ijaz; Zubair, Muhammad; Adeel, Shahid; Yousaf, Muhammad; Ahmad, Matloob; Iqbal, Munwar; Usman, Muhammad; Zuber, Muhammad; Mansha, Asim (Asian Journal of Chemistry, 2013)
Advance oxidation processes hold great promise for the degradation and mineralization of textile dye and effluent. The degradation of C.I reactive yellow 145 dye at different conditions was carried out in order to assess the effectiveness and feasibility of the combined UV/H2O2 system for purification of water. The operating parameters such as hydrogen peroxide dose, pH value, UV exposure time and initial concentration of reactive yellow 145 dye were evaluated. The degradation efficiency increased nonlinearly with increasing UV light intensity and hydrogen peroxide dosage. The observation of obtained results clearly demonstrated the importance of choosing the optimum degradation parameters to obtain a high degradation rate, which was essential for any practical application of photo degradation process. The degradation of reactive yellow 145 observed up to 98 % for the optimized levels of operation variables. It has been concluded that this process can be used as an efficient and environmental friendly technique for effluent treatment of industrial wastewater containing dyes from textile industry. Development of this technology is of great importance as the existing technology in textile industry is not efficient for treating the wastewaters resulting in discharge of coloured water into rivers and public sewage system which is a health hazard.